2021
DOI: 10.3389/fnins.2021.573858
|View full text |Cite
|
Sign up to set email alerts
|

Brain Structural and Functional Reorganization in Tinnitus Patients Without Hearing Loss After Sound Therapy: A Preliminary Longitudinal Study

Abstract: Sound therapy is one of the most common first-line treatments for idiopathic tinnitus. We aimed to investigate the brain structural and functional alterations between patients with idiopathic tinnitus without hearing loss (HL) and healthy controls (HCs) and between patients before and after sound therapy (narrow band noise). Structural and resting-state functional images were acquired from 13 tinnitus patients without HL and 18 HCs before and after 6 months of narrow band sound therapy (only patients received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 70 publications
2
21
0
Order By: Relevance
“…Regarding the FC changes in the lVN (nonprimary regions of the visual cortex), consistent with one of our prior studies (Chen et al, 2021b), we speculated that because of the increased compensatory stimulation between the auditory and visual networks caused by tinnitus through the thalamus, the relay station (Chen et al, 2019), the increased intranetwork FC in the MOG may reflect an abnormal overactive state of the visual network in tinnitus patients. Meanwhile, we also observed decreased intranetwork FC in the DAN.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Regarding the FC changes in the lVN (nonprimary regions of the visual cortex), consistent with one of our prior studies (Chen et al, 2021b), we speculated that because of the increased compensatory stimulation between the auditory and visual networks caused by tinnitus through the thalamus, the relay station (Chen et al, 2019), the increased intranetwork FC in the MOG may reflect an abnormal overactive state of the visual network in tinnitus patients. Meanwhile, we also observed decreased intranetwork FC in the DAN.…”
Section: Discussionsupporting
confidence: 88%
“…The DAN is involved in visual attention (Gitelman, 2003). Previous studies have shown increased FC between the DAN and other RSNs (such as the DMN; Chen et al, 2021b; Schmidt et al, 2013), and the authors suggested that this change could be a compensatory attempt to transfer the phantom stimulus to the limbic system (Golm, Schmidt‐Samoa, Dechent, & Kröner‐Herwig, 2013; Ooms et al, 2013). Thus, increased FC in the DAN of IG patients may represent abnormal compensation caused by the enhanced connectivity between the DAN and other RSNs, although the exact mechanism is still not clear.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations